2019
DOI: 10.3390/ijms20081984
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Modulating Anti-oxidant Stress Activity of Gastrodin on Nonalcoholic Fatty Liver Disease Larval Zebrafish Model

Abstract: Non-alcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) is the most common chronic liver disease in the world. However, there are still no drugs for NAFLD/NASH in the market. Gastrodin (GAS) is a bioactive compound that is extracted from Gastrodia elata, which is used as an active compound on nervous system diseases. Recent reports showed that GAS and Gastrodia elata possess anti-oxidant activity and lipid regulating effects, which makes us curious to reveal the anti-NAFLD effect of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Thereby, gastrodin has been considered as a potential therapeutic agent for diverse diseases such as Tourette syndrome, 7 myocardial infarction, 8 alcoholic liver disease 6,9 and acute lung injury. Thereby, gastrodin has been considered as a potential therapeutic agent for diverse diseases such as Tourette syndrome, 7 myocardial infarction, 8 alcoholic liver disease 6,9 and acute lung injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, gastrodin has been considered as a potential therapeutic agent for diverse diseases such as Tourette syndrome, 7 myocardial infarction, 8 alcoholic liver disease 6,9 and acute lung injury. Thereby, gastrodin has been considered as a potential therapeutic agent for diverse diseases such as Tourette syndrome, 7 myocardial infarction, 8 alcoholic liver disease 6,9 and acute lung injury.…”
mentioning
confidence: 99%
“…forth. Thereby, gastrodin has been considered as a potential therapeutic agent for diverse diseases such as Tourette syndrome, 7 myocardial infarction, 8 alcoholic liver disease 6,9 and acute lung injury. 10 However, the effects of gastrodin on COPD were not studied previously.…”
mentioning
confidence: 99%
“…The Nrf2 activation mediated by herbal medicine can improve NAFLD via inhibiting oxidative stress pathway. It has been reported that scutellarin (a flavonoid glycoside), swertiamarin (a secoiridoid glycoside) (Yang Y. et al, 2019) and gastrodin (isolated from Gastrodia elata Bl) enhance Nrf2-mediated antioxidant system via activating the mRNA and protein levels of PPARg and its coactivator-1a, HO-1, GST, and NQO1 expressions (Ahmad et al, 2019), thus ameliorate NAFLD. Isochlorogenic acid B [extracted from Laggera alata (Asteraceae)] shows its protective effects on fibrosis in NASH by Nrf2 signaling pathway, and reverse the downregulation of miR-122 level and upregulation of hepatic HIF-1a expression to inhibit multiple profibrogenic factors (COL1a1, MCP-1, LOX, TGF-b1, and TIMP-1) (Liu et al, 2019c).…”
Section: Oxidative Stress Action Involves In Herbal Medicine Modulatimentioning
confidence: 99%
“…It has been indicated that herbal medicine has exerted the protective effects against the progression from hepatic steatosis to steatohepatitis and the underlying mechanism have been proved to be involved in inhibiting the inflammatory signaling pathway as shown in Figure 2, thereby regulating dyslipidemia and improving liver function in NAFLD. Many herbal medicine (including herbal formula, crude extract and pure bioactive compound form medicinal plants) possessed antiinflammatory properties for slowing down the NAFLD progression, such as Sinai san dection (Zhang et al, 2005), Hugan Qingzhi tablet (Tang et al, 2015), betulinic acid (Kim et al, 2019b), Alisma orientalis , gastrodin (Ahmad et al, 2019), the peel extract of Citrus aurantium L. (Rutaceae) (Han et al, 2019) and swertiamarin (Yang Y. et al, FIGURE 1 | The lipid mechanistic insight into the anti-NAFLD effects of herbal medicine. NAFLD, Non-alcoholic fatty liver disease.…”
Section: Herbal Medicine Ameliorates the Hepatic Inflammationmentioning
confidence: 99%
“…It has the characteristics of multipathway and multitarget and can be used for holistic treatment from different levels because of its remarkable curative effect and small side effects [24][25][26]. More and more studies show that TCM is effective in treating NAFLD [27,28]. It is found that the extract of TCM or effective components can address not only NAFLD but also other illnesses of the metabolic syndrome, such as obesity, diabetes, and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%